Postoperative rehabilitation after deep brain stimulation surgery for movement disorders. Issue 3 (March 2018) - Allert, Niels; Cheeran, Binith; Deuschl, Günther; Barbe, Michael T.; Csoti, Ilona; Ebke, Markus; Glaser, Martin; Kang, Jun-Suk; Kelm, Stefan; Krack, Paul; Kroth, Julia; Jobst, Ulrich; et al.
Highlights: We summarize actual clinical practice for postoperative care of DBS patients. Strategies to quantify and improve individual postoperative care are discussed. Optimized rehabilitative framework leads to more effective clinical outcome of DBS. Abstract: Deep brain stimulation (DBS) is a highly efficient, evidence-based therapy for a set of neurological and psychiatric conditions and especially movement disorders such as Parkinson's disease, essential tremor and dystonia. Recent developments have improved the DBS technology. However, no unequivocal algorithms for an optimized postoperative care exist so far. The aim of this review is to provide a synopsis of the current clinical practice and to propose guidelines for postoperative and rehabilitative care of patients who undergo DBS. A standardized work-up in the DBS centers adapted to each patient's clinical state and needs is important, including a meticulous evaluation of clinical improvement and residual symptoms with a definition of goals for neurorehabilitation. Efficient and complete information transfer to subsequent caregivers is essential. A coordinated therapy within a multidisciplinary team (trained in movement disorders and DBS) is needed to achieve the long-range maximal efficiency. An optimized postoperative framework might ultimately lead to more effective results of DBS.